Pengaruh Terpaan Berita Suap Pemeriksa di Detik. Com terhadap Sikap Pemeriksa Pada Badan Pemeriksa Keuangan Republik Indonesia Perwakilan Provinsi Sumatera Utara - Fanani Sari Putri (Universitas Medan Area, 2019)
The objective of the research was to analyze the influence of news reporting about the case of bribery to the investigator of BPK RI (The Audit Board of the Republic of Indonesia) on Detik.com on the attitude of the auditors at BPK RI in North Sumatera Province, and to analyze the influence of individual as well as social factors on the auditors’ attitude in carrying out the ethical code of auditing. It employed quantitative approach with correlational method using SPSS. Total Sampling technique was applied to collect the samples; indicating that the whole population was taken as the samples, namely 98 respondents. The result of the research showed that there was positive impact and significant correlation. The results of the research demonstrated that the news reporting by its frequency, duration, credibility, content and design about the bribery case of an auditor of BPK RI influenced the attitude of the auditors in carrying out auditing procedures and there were individual and social factors as the control variables which increased the correlation and influenced the attitude of the auditor.